(untitled) (Bangladesh Journal of Agricultural Research, 2008)
A study was undertaken to determine the prevalence of black point and percentages of germination, moisture content and different fungi associated with wheat seeds during storage in different types of container. Seeds of a widely cultivated variety Kanchan were stored in five types of containers viz., âdole’(bamboo made), earthen pitcher, tin container, polyethylene bag and refrigerator (10Â°C) for ten months at room temperature. Samples were taken at monthly interval beginning from the month of April (prior to storage). The seed moisture content and black point severity were found highest in dole resulting in the lowest percentage of seed germination. The highest germination percentage was observed under storage in refrigerator followed by polyethylene bag, tin container and earthen pitcher. The moisture content and black point infection increased and seed germination decreased with the increase of storage period. Prior to storage in April, the seed germination was 95%, which decreased to about 75% at the end often months of storage (in January). Various fungal flora associated with wheat seeds differed in their prevalence depending on the length of storage period and types of container used for storage. The population of field fungi viz., Alternaria alternata, Aiternaria triticina, Bipolaris sorokiniana, Cladosporium cladosporioides, Curvularia lunata, Epicoccum purpurascens and Fusarium spp. decreased while that of storage fungi viz., Aspergillus, Chaetomium, Nigrospora, Penicillium and Rhizopus increased with the progress of storage period. Key Words: Storage, seed quality, wheat. doi:10.3329/bjar.v33i3.1606 Bangladesh J. Agril. Res. 33(3) : 469-477, September 2008